Considering Commercial Vessels as Potential Vectors of Stony Coral Tissue Loss Disease - Rosenau, Nicholas A.; Gignoux-Wolfsohn, Sarah; Everett, Richard A.; Miller, A. Whitman; Minton, Mark S.; Ruiz, Gregory M. (Frontiers in Marine Science, 2021)
The reason(s) for the rapid spread of stony coral tissue loss disease (SCTLD) in the greater Caribbean region has yet to be elucidated. Ocean currents have been examined as a potential contributor particularly along the Florida Reef Tract, however, currents alone do not explain the disease’s spatiotemporal pattern of spread across geographically disparate locations, resulting in several hypotheses about possible vectors for observed dispersal and spread. Despite regulatory and management strategies intended to limit coastal marine invasion risks, vessel-borne disease transport via ballast water and hull biofouling are under examination given the high commercial vessel traffic in the region. Current work is evaluating the performance of these measures, including spatio-temporal analyses of vessel movement and ballast water management, analysis of SCTLD reports, and ex-situ transmission of ballast water treatment (UV-sterilization) experiments. Here, we discuss the current state of knowledge about ballast water as a potential contributor to transmission of SCTLD in the greater Caribbean and provide a framework for future research.